Hydrogen production from CH4 dry reforming over bimetallic Ni–Co/Al2O3 catalyst - Siang, Tan Ji; Singh, Sharanjit; Omoregbe, Osaze; Bach, Long Giang; Phuc, Nguyen Huu Huy; Vo, Dai-Viet N. (Elsevier Ltd., 2018)
Bimetallic 5%Ni–10%Co/Al2O3 catalyst was synthesized using impregnation method and evaluated for methane dry reforming reaction at different reaction temperatures. NiO, Co3O4 and spinal metal aluminates, namely, CoAl2O4 and NiAl2O4 phases were formed on γ-Al2O3 support surface during calcination process. 5%Ni–10%Co/Al2O3 catalyst exhibited reasonable surface area of 86.93 m2 g−1 with small crystallite dimension of less than 10 nm suggesting that both Co3O4 and NiO phases were finely dispersed on the surface of support in agreement with results from scanning electron microscopy (SEM) measurement. Temperature-programmed calcination measurement indicates the complete thermal decomposition and oxidation of metal precursors, viz. Ni(NO3)2 and Co(NO3)2 to metal oxides and metal aluminates at below 700 K. Both CH4 and CO2 conversions were stable over a period of 4 h on-stream and attained an optimum at about 67% and 71%, respectively at 973 K whilst H2 selectivity and yield were higher than 49%. The ratio of H2/CO was always less than unity for all runs indicating the presence of reverse water–gas shift reaction. The activation energy for CH4 and CO2 consumption was computed as 55.60 and 40.25 kJ mol−1, correspondingly. SEM micrograph of spent catalyst detected the formation of whisker-like carbon on catalyst surface whilst D and G bands characteristic for the appearance of amorphous and graphitic carbons in this order were observed on surface of used catalyst by Raman spectroscopy analysis. Additionally, the percentage of filamentous carbon was greater than that of graphitic carbon.